An Inter–professional Antiracist Curriculum Is Paramount to Addressing Racial Health Inequities. Issue 1 (2022) - Mitchell, L. Kate; Watson, Maya K.; Silva, Abigail; Simpson, Jessica L.
Abstract: Legal, medical, and public health professionals have been complicit in creating and maintaining systems that drive health inequities. To ameliorate this, current and future leaders in law, medicine, and public health must learn about racism and its impact along the life course trajectory and how to engage in antiracist practice and health equity work.